2008
DOI: 10.1158/1078-0432.ccr-07-4913
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Imatinib with Human Organic Ion Carriers

Abstract: Purpose: The activity of imatinib in leukemia has recently been linked with expression of the organic cation transporter 1 (OCT1) gene SLC22A1. Here, we characterized the contribution of solute carriers to imatinib transport in an effort to further understand mechanisms involved in the intracellular uptake and retention (IUR) of the drug. Experimental Design: IUR of [ 3 H]imatinib was studied in Xenopus laevis oocytes and HEK293 cells expressing OATP1A2, OATP1B1, OATP1B3, OCT1-3, OCTN1-2, or OAT1-3. Gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
182
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 41 publications
(53 reference statements)
9
182
1
6
Order By: Relevance
“…24 In the human intestine, OATP1A2 is expressed on the apical brush-border membrane of human enterocytes, 45 which suggests that net absorption of IM may reflect a situation in which there is greater uptake by SLCO1A2 (OATP1A2) than efflux by ABCG2 (BCRP). In this study, SLCO1A2 genotyping was not performed because SNPs that affect OATP1A2 transport activity are not typically found in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In the human intestine, OATP1A2 is expressed on the apical brush-border membrane of human enterocytes, 45 which suggests that net absorption of IM may reflect a situation in which there is greater uptake by SLCO1A2 (OATP1A2) than efflux by ABCG2 (BCRP). In this study, SLCO1A2 genotyping was not performed because SNPs that affect OATP1A2 transport activity are not typically found in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Although IM is a substrate of OCT1, 15,22,23 no association between IM and SLC22A1 286C4T or 1498G4A, variants not common in the Japanese population, was previously observed. 24,25 In addition, in vitro studies have shown that organic anion-transporting polypeptide 1B3 (OATP1B3), which is encoded by SLCO1B3, contributes to IM uptake into hepatocytes. 24 However, to date, the influence of SLCO1B3 SNPs on the pharmacokinetics of IM has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative clinical significance of potential imatinib uptake transporters has extensively been investigated in the last decade as reflected by the numerous (pre-) clinical studies that have been conducted to investigate their role in the pharmacokinetics and/or pharmacodynamics of imatinib (Thomas et al, 2004;Crossman et al, 2005;White et al, 2006White et al, , 2007White et al, , 2010Hu et al, 2008;Wang et al, 2008;White and Hughes, 2012;Nies et al, 2014). SLC22A1, also referred to as organic cation transporter (OCT) 1, has frequently been implicated in the intracellular uptake and disposition of imatinib in CML cells (Thomas et al, 2004;White et al, 2006), although controversy exists with regard to its precise role (Burger et al, 2013;Nies et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are held responsible for the cytotoxicity of platin derivatives and are predictors of responses to small molecules [11,[22][23][24]. Downregulation in HCC could be responsible for a worse or lacking response towards platin treatment.…”
Section: Discussionmentioning
confidence: 99%